Lachman's case studies in anatomy - Cahill, Donald R. (Oxford University Press, 1997)
This popular collection of fifty anatomical case studies, now revised by a leading clinical anatomist, covers all the major regions of the body: head and neck, thorax, abdomen, pelvis and perineum, and limbs. Each case study includes the patient's history, physical exam results, diagnosis, therapy, and a discussion of the findings from the anatomical viewpoint. The discussion becomes the heart of each case by skillfully evolving the logic required to make a diagnosis and prescribe therapy. The cases are ably designed to encourage critical thinking and problem solving